Development of Wireless Planting Robot for Sowing Seeds, Watering and Fertilizing Plantations - Ismail, Zakwan; Ahmad Po'ad , Farhana (Evolution in Electrical and Electronic Engineering, 2022)
Agriculture is the art and science of cultivating soil, growing crops, and raising livestock. At present, agriculture is developing rapidly, and the production of various machinery and equipment has encouraged the development of agriculture. The main objective of this project is to develop an economical agriculture robot for smallholders that use advanced technology to make local agriculture more sustainable. The combination of wireless controller technology and the robot is to help humans to do multi work at the same time and to reduce the time but increase the production. A portable robot that works for seeding, watering and fertilizing as well as being controlled using a wireless PS2 controller. The data generated through the tests conducted show that all the specified functions are running smoothly. Instructions received through the wireless controller are also well received by the robot. Based on the results and analysis done, this project shows positive results and is according to the objective. This robot can also be upgraded by increasing the amount of output available where this robot only uses a few buttons on the controller.